2018
DOI: 10.1111/1747-0080.12444
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary behaviours and perceived physical and mental health status among Korean adolescents

Abstract: Our data suggest that existing encouraged dietary habits mostly have beneficial effects on perceived physical and mental health in Korean adolescents. However, the cross-sectional study design prevents our ability to assess causal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 48 publications
1
39
0
1
Order By: Relevance
“…Within the studies included to a systematic review, there were such of various sample size, as some of them assessed less than 1000 respondents [5,13,14,17,23,29], but other studied large population-based groups, as in the case of almost 15,000 participants of Global School-Based Health Survey [1], or over 65,000 participants from South Korea, assessed in two studies [7,21]. Based on the presented data, it may be supposed that some of the included studies assessed populations which overlapped, as for indicated South Korean studies [7,21], but for the presented systematic review, they were treated as a separate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the studies included to a systematic review, there were such of various sample size, as some of them assessed less than 1000 respondents [5,13,14,17,23,29], but other studied large population-based groups, as in the case of almost 15,000 participants of Global School-Based Health Survey [1], or over 65,000 participants from South Korea, assessed in two studies [7,21]. Based on the presented data, it may be supposed that some of the included studies assessed populations which overlapped, as for indicated South Korean studies [7,21], but for the presented systematic review, they were treated as a separate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Included studies were conducted mainly in various Asian countries [7,13,14,21,23,25], European countries [5,8,11,15,29], Australia [9,10,17,18], but also Ghana [6] and combined population of the Botswana, Kenya, Seychelles, Uganda, Tanzania and Zambia [1]. The assessed participants were recruited mainly in a school-based manner [5,6,7,8,9,15,21,23,25,29], while for majority of studies the samples were population-based, but also in case of one study, there was a specific group of socially deprived young people included [11].…”
Section: Discussionmentioning
confidence: 99%
“…There has been less research among adolescent and young adult populations than that of adults and children . Adolescents and young adults are establishing behaviours that can track in to adult life and are at a stage when they are very receptive to their environment and can readily adopt high risk behaviours.…”
mentioning
confidence: 99%
“…There has been less research among adolescent and young adult populations than that of adults and children. 25 Adolescents and young adults are establishing behaviours that can track in to adult life and are at a stage when they are very receptive to their environment and can readily adopt high risk behaviours. Park et al 25 investigate the association between dietary habits and perceived mental and physical health among a representative sample of Korean youths with data from an online self-report survey conducted by the Korea Centres for Disease Control and Prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation